Single-molecule live-cell imaging reveals RecB-dependent function of DNA polymerase IV in double strand break repair. Issue 15 (20th July 2020) - Henrikus, Sarah S; Henry, Camille; McGrath, Amy E; Jergic, Slobodan; McDonald, John P; Hellmich, Yvonne; Bruckbauer, Steven T; Ritger, Matthew L; Cherry, Megan E; Wood, Elizabeth A; Pham, Phuong T; Goodman, Myron F; et al.
Abstract: Several functions have been proposed for the Escherichia coli DNA polymerase IV (pol IV). Although much research has focused on a potential role for pol IV in assisting pol III replisomes in the bypass of lesions, pol IV is rarely found at the replication fork in vivo . Pol IV is expressed at increased levels in E. coli cells exposed to exogenous DNA damaging agents, including many commonly used antibiotics. Here we present live-cell single-molecule microscopy measurements indicating that double-strand breaks induced by antibiotics strongly stimulate pol IV activity. Exposure to the antibiotics ciprofloxacin and trimethoprim leads to the formation of double strand breaks in E. coli cells. RecA and pol IV foci increase after treatment and exhibit strong colocalization. The induction of the SOS response, the appearance of RecA foci, the appearance of pol IV foci and RecA-pol IV colocalization are all dependent on RecB function. The positioning of pol IV foci likely reflects a physical interaction with the RecA* nucleoprotein filaments that has been detected previously in vitro . Our observations provide an in vivo substantiation of a direct role for pol IV in double strand break repair in cells treated with double strand break-inducing antibiotics.